แนวทางการพัฒนาการนิเทศภายในสถานศึกษา ศูนย์พัฒนาคุณภาพการศึกษาที่ 3 สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาขอนแก่น เขต 3 - หาญชนะ, นัฐวุฒิ; ศิริปุณยนันท์, ธนาศักดิ์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด, 2023)
บทความวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาสภาพปัจจุบัน สภาพที่พึ่งประสงค์และความต้องการจำเป็นของการนิเทศภายในสถานศึกษา ศูนย์พัฒนาคุณภาพการศึกษาที่ 3 สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาขอนแก่น เขต 3 กลุ่มตัวอย่าง ได้แก่ ผู้บริหารสถานศึกษาและครูซึ่งปฏิบัติหน้าที่รวมทั้งสิ้น 59 คน โดยใช้แบบสอบถามในการรวบรวมข้อมูล สถิติที่ใช้ในการวิจัย ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และค่าดัชนีความต้องการจำเป็น                 ผลการวิจัยพบว่า สภาพปัจจุบันของการนิเทศภายในโดยรวมอยู่ในระดับมาก สภาพที่พึงประสงค์ของการนิเทศภายในโดยรวมอยู่ในระดับมากที่สุด ความต้องการจำเป็นของการนิเทศภายใน เรียงลำดับจากมากไปหาน้อย ได้แก่ ด้านการเวางแผนและพัฒนาการนิเทศภายในโรงเรียน เฉลี่ยที่ 0.24 รองลงมา ได้แก่ ด้านการเผยแพร่และขยายผลอย่างต่อเนื่องและยั่งยืนภายในโรงเรียน เฉลี่ยที่ 0.20 และด้านการติดตามและประเมินผลการนิเทศภายในโรงเรียน เฉลี่ยที่ 0.16  ตามลำดับ โดยได้แนวทางในการพัฒนาการนิเทศภายในทั้งหมด 25 แนวทาง ได้แก่ ด้านการวิเคราะห์สภาพปัจจุบันความต้องการในการนิเทศภายในโรงเรียน มี 5 แนวทาง ด้านการวางแผนและพัฒนาการนิเทศภายในโรงเรียน มี 5 แนวทาง  ด้านการปฏิบัติการนิเทศภายในโรงเรียน มี 5 แนวทาง ด้านการติดตามและประเมินผลการนิเทศภายในโรงเรียน มี 5 แนวทาง ด้านการเผยแพร่ขยายผลอย่างต่อเนื่องและยั่งยืนภายในโรงเรียน มี 5 แนวทาง โดยผลการประเมินความเหมาะสมและความเป็นไปได้อยู่ในระดับมากที่สุดทุกด้าน            This research article aims to Study the current condition The desired conditions and necessary needs of supervision within educational institutions. Educational Quality Development Center 3, under the Office of Khon Kaen Primary Educational Service Area 3, The sample groups used in the research are total of 59 educational institution administrators and teachers performing their duties used a questionnaire to collect data. The statistics used in the research include: frequency, percentage, mean, standard deviation and the index of essential needs.            The research results found that: The current condition of internal supervision is overall at a high level. The desirable conditions of internal supervision were overall at the highest level. Necessary needs of internal supervision. Arranged from highest to lowest, namely the planning and development of supervision within the school, with an average of 0.24, followed by the aspect of dissemination and expansion of results continuously and sustainably within the school, with an average of 0.20. and the monitoring and evaluation of supervision within the school, with an average of 0.16, respectively, with a total of 25 guidelines for the development of internal supervision, including the analysis of the current conditions and needs for supervision within the school, with 5 guidelines, the planning and development of internal supervision The school has 5 guidelines. In terms of supervision operations within the school, there are 5 guidelines. In terms of monitoring and evaluating supervision within the school, there are 5 approaches. In terms of disseminating and expanding results continuously and sustainably within the school, there are 5 approaches. According to the results of the evaluation of suitability and feasibility. Found to be at the highest level in every aspect.